Bone morphogenetic proteins, activins, and growth and differentiation factors in tumor immunology and immunotherapy resistance - Ganjoo, Shonik; Puebla-Osorio, Nahum; Nanez, Selene; Hsu, Ethan; Voss, Tiffany; Barsoumian, Hampartsoum; Duong, Lisa K.; Welsh, James W.; Cortez, Maria Angelica (Frontiers in Immunology, 2022)
The TGF-β superfamily is a group of secreted polypeptides with key roles in exerting and regulating a variety of physiologic effects, especially those related to cell signaling, growth, development, and differentiation. Although its central member, TGF-β, has been extensively reviewed, other members of the family—namely bone morphogenetic proteins (BMPs), activins, and growth and differentiation factors (GDFs)—have not been as thoroughly investigated. Moreover, although the specific roles of TGF-β signaling in cancer immunology and immunotherapy resistance have been extensively reported, little is known of the roles of BMPs, activins, and GDFs in these domains. This review focuses on how these superfamily members influence key immune cells in cancer progression and resistance to treatment.